2008
DOI: 10.1111/j.1600-0501.2007.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Injectable calcium phosphate cement as a graft material for maxillary sinus augmentation: an experimental pilot study

Abstract: CaP cement is indeed effective to stimulate bone formation in the sinus elevation procedure. Nevertheless, additional improvements in the cement composition are required to allow final clinical utilization of the material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The osseoinductive effect of rhBMP-2 depends on the amount of cells in the region of augmentation which in turn depends on the species, the age and the vascularity of the area (Terheyden et al, 1999;Yamaji et al, 2007). Sinus-lift procedures in a sheep model are a reliable method for evaluating bone formation (Aral et al, 2008;Estaca et al, 2008). Several studies have reported the positive effects that certain BMPs have on bone generation in different animal trials (Allegrini et al, 2003(Allegrini et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…The osseoinductive effect of rhBMP-2 depends on the amount of cells in the region of augmentation which in turn depends on the species, the age and the vascularity of the area (Terheyden et al, 1999;Yamaji et al, 2007). Sinus-lift procedures in a sheep model are a reliable method for evaluating bone formation (Aral et al, 2008;Estaca et al, 2008). Several studies have reported the positive effects that certain BMPs have on bone generation in different animal trials (Allegrini et al, 2003(Allegrini et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BoneSource TM is indicated for the repair of neurosurgical burr holes, contiguous craniotomy cuts and other cranial defects with a surface area no larger than 25 cm 2 per a defect. In addition, it may be used in the sinus region for facial augmentation [127,562] and the formulation can be supported by metal hardware [127]. In dogs, BoneSource TM was employed to supplement the supraorbital ridge and to augment skull base defects [563].…”
Section: Biomedical and Clinical Applicationsmentioning
confidence: 99%
“…For example, BoneSource TM is indicated for the repair of neurosurgical burr holes, contiguous craniotomy cuts and other cranial defects with a surface area no larger than 25 cm 2 per a defect. In addition, it may be used in the sinus region for facial augmentation [103,490] and the cement can be supported by metal hardware [103]. In dogs, BoneSource TM was employed to supplement the supraorbital ridge and to augment skull base defects [491].…”
Section: Craniofacial and Maxillofacial Applicationsmentioning
confidence: 99%